Introduction to criminal investigation : processes, practices and thinking - Gehl, Rod; Plecas, Darryl; Justice Institute of British Columbia; BC Open Textbook Project; BCcampus (Justice Institute of British Columbia, 2017)
"Introduction to Criminal Investigation, Processes, Practices, and Thinking, as the title suggests, is a teaching text describing and segmenting criminal investigations into its component parts to illustrate the craft of criminal investigation. Delineating criminal investigation within the components of task-skills and thinking-skills, this book describes task-skills such incident response, crime scene management, evidence management, witness management, and forensic analysis, as essential foundations supporting the critical thinking-skills of offence validation and theory development for the creation of effective investigative plans aimed at forming reasonable grounds for belief. The goal of the text is to assist the reader in forming their own structured mental map of investigative thinking practices"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed on October 17, 2017).
Keywords: Criminal investigation; Electronic books